Sinopticon : a celebration of Chinese science fiction - Ni, Xueting Christine, 1981-; Ni, Xueting Christine, 1981-; Shi, Gu; Song, Han; Jingfag, Hao; Yu, Nian; Jinkang, Wnag; Haihong, Zhao; Fei, Tang; Boyong, Ma; Wu, Anna; Que, A. (Solaris, 2021)
Presents a collection of the best Chinese science fiction stories from thirteen writers, translated into English for the first time.